2007
DOI: 10.1183/09031936.00144106
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor expression is reduced in skeletal muscle in COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is a multiorgan systemic disease. The systemic features are skeletal muscle weakness and cachexia, the latter being associated with systemic inflammation. The exact mechanisms underlying skeletal muscle dysfunction in COPD remain obscure. Recent evidence suggests involvement of the peroxisome proliferatoractivated receptors (PPARs) and PPAR-c coactivator (PGC)-1a in regulation of skeletal muscle morphology and metabolism, and mitochondrial transcription factor A (TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
103
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 37 publications
12
103
2
2
Order By: Relevance
“…4) [196]. reduced expression of PGC-1a [197]. Reduced PPAR-a expression is correlated with cachexia and systemic inflammation, suggesting that PPAR-a agonists, such as clofibrate and fenofibrate, may have therapeutic potential in treating the systemic features of COPD.…”
Section: Ppar Agonistsmentioning
confidence: 99%
“…4) [196]. reduced expression of PGC-1a [197]. Reduced PPAR-a expression is correlated with cachexia and systemic inflammation, suggesting that PPAR-a agonists, such as clofibrate and fenofibrate, may have therapeutic potential in treating the systemic features of COPD.…”
Section: Ppar Agonistsmentioning
confidence: 99%
“…Physical inactivity induces several adaptive changes in skeletal muscles, including reduced proportions of type I fi bers, attenuation of oxidative enzyme capacity, regulators of mitochondrial biogenesis (PPARs and PGC-1α), fi ber atrophy, reduction of antioxidant enzyme levels and lower capillary density (Franssen et al 2002;Lawler et al 2003;Remels et al 2007). These changes, collectively known as musculoskeletal deconditioning, result in signifi cant reductions in skeletal muscle strength and endurance.…”
Section: Inactivitymentioning
confidence: 99%
“…26 and reductions in peroxisome proliferator-activated receptors (involved in mitochondrial biogenesis). 43 Gosker et al 21 recently confirmed that the severity of COPD is associated with reductions in the proportion of type I fibres. The aforementioned factors together with the finding that lactic acidosis occurs earlier during exercise in COPD patients compared with healthy subjects, 33 may partly explain why COPD patients fatigue quicker and experience exercise intolerance.…”
Section: Skeletal Muscle Dysfunctionmentioning
confidence: 77%
“…In addition, it was recently hypothesised that resistance training may only induce brief 5'AMP-activated protein kinase (AMPK) activation (possibly not at all), resulting in limited AMPK-dependent adaptations such as mitochondrial biogenesis. 51 With the skeletal muscle of COPD patients already exhibiting reduced mitochondrial biogenesis, oxidative enzymes and oxidative capacity, 18,43 the possibility that resistance training may exacerbate this situation requires clarification.…”
Section: Resistance Training and Molecular Adaptations In Skeletal Mumentioning
confidence: 99%